Application of the PBL Model on Temperature and Heat Concepts to Student Learning Outcomes - Andini Pratiwi M. Mahmud; Muhammad Yusuf; Tirtawaty Abdjul; Masrid Pikoli; Nova Elysia Ntobuo; Dewi Diana Paramata (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze the application of the Problem-Based Learning (PBL) learning model on temperature and heat concepts on student learning outcomes. This research is experimental research, with the research design used being a one-group pretest-posttest design. The sampling technique used in this research was the total sampling technique. The population in this study was all class VII of MTs Al-Khairaat Kwandang for the 2023/2024 academic year. The sample in this study consisted of 3 classes, namely Class VII B as the experimental class, Class VII A as replication 1, and Class VII C as replication 2, where the experimental and replication classes were determined randomly by drawing lots. Research data was collected using test techniques, then the data was analyzed using descriptive statistics and inferential statistics, which include normality tests, hypothesis tests, and n-gain analysis. The results obtained for all sample classes, the average for class VII students is greater than the Criteria for Achieving Learning, which is shown by the average value of the experimental class of 85.49, replication 1 of 84.18, and replication 2 of 82.92. Based on the results of the course average normalized gain obtained by the experimental class was 0.78, replication 1 was 0.76, and replication 2 was 0.75, which means that all sample classes are in the high category. Thus, the PBL learning model has a significant effect on student learning outcomes in concepts of temperature and heat.